Pengaruh Konfigurasi Politik Hukum Terhadap Karakter Produk Hukum - Lintje Anna Marpaung (Law Faculty of Universitas Bandar Lampung, 2012)
Law structure can expand in a condition any political configuraton marked by efficacy of making of unification and codification punish as seeing in Program Legislation National. This Matter happened ketidak synchronize between structure punish with function punish as referred above because of because trouble or intervention of political actions. Law sometime do not upheld caused by intervention power of politics. Law product show his it with the happening of pattern refuse to draw between law product which responsive with character and law product which with character Conservative. In this time indicate that certain political situation will be able to bear product punish with certain character also. This matter theoretically, political system dikotomis of democracy will yield responsive law product. While autoritary political system configuraton will yield conservative law product / orthodox. Conclusion of the public canÂ directly hooked;correlated under study arrangement of law about governance of area in Indonesia.